Design， Modeling and Simulation of Pendulum Indexing Cam-planetary Gear Composite Mechanism - Wang Shilong; Ji Sanyou; Tong Liang (Jixie chuandong)
A new type of indexing cam-planetary gear composite mechanism is designed and studied. The input shaft is coaxial with the output shaft， the input shaft is fixedly connected to the swing rod， the swing rod is hinged to the planetary gear shaft， and the planetary gear， the two swing arms and the planetary gear shaft are fixedly connected. The swinging rod rotates with the input shaft， and the rollers on the two swinging rods are kept in contact with the two cams respectively. The contact point changes continuously with the rotation of the swinging rod， and the swinging arm rotates relative to the swinging rod to drive the planetary wheel connected thereto to swing. Finally， the intermittent movement of the center wheel is realized， that is， the indexing movement. The working condition parameters of the mechanism motion are defined. According to the specific parameters， the actual contour equation of the cam is designed， and the 3D modeling and motion simulation of the mechanism are completed， which verifies the correctness of the design modeling process.